The toxic intensity of industrial production: Global patterns, trends, and trade policy - Hettige, Hemamala; Wheeler, David; Lucas, R.E.B. (American Economic Review, 1992)
This paper exploits a newly developed data set to investigate recent changes in the international distribution of industrial pollution. In particular, the authors examine three issues: (1) the relationship between the toxic intensity of industrial production and the level of economic development, (2) the impact of OECD environmental regulation on global changes in toxic intensity, and (3) the relationship between trade policy and the toxic intensity of industrial production in LDC's. 10 refs.